THU0035 A cd8 alpha-negative subset of cd4+slamf7+ cytotoxic t cells is expanded in patients with igg4-related disease and decreases following glucocorticoid treatment. (12th June 2018) - Della Torre, E.; Bozzalla Cassione, E.; Sciorati, C.; Lanzillotta, M.; Bozzolo, E.; Rovati, L.; Mattoo, H.; Perugino, C.; Stone, J.; Dagna, L.; Pillai, S.; Manfredi, A.
Abstract : Background: IgG4-Related Disease (IgG4-RD) is a fibro-inflammatory disorder characterised by tumefactive lesions, frequent elevation of serum IgG4 levels, and tissue fibrosis. 1 Glucocorticoids represent the treatment of choice to induce IgG4-RD remission but their effect on the cells orchestrating the disease remains unknown. 1 We recently describerd an unconventional population of clonally expanded CD4 + SLAMF7 + cytotoxic T effector memory (TEM ) cells (CD4 + CTLs) and causally linked it to IgG4-RD in view of their capacity to secrete pro-fibrotic molecules and to infiltrate affected organs. 2–4 Objectives: In order to better clarify the mechanisms of action of glucocorticoids in IgG4-RD and the pathogenic relevance of CD4 + CTLs, we herein aim to describe the effects of corticosteroid treatment on CD4 + CTLs. Methods: CD8α, granzyme A, perforin, and SLAMF7 expression within the effector/memory compartment of CD45RO (TEM ) and CD45RA (TEMRA ) CD4 + T cells was quantified by flow cytometry in 18 active IgG4-RD patients at baseline and after 6 months of glucocorticoid treatment. Eighteen healthy subjects were studied as controls. Next-generation sequencing of the T-cell receptor α and β chain gene was performed on circulating CD4 + CTLs in patients with IgG4-RD before and after treatment, and in affected tissues. Results: Circulating CD4 + TEM and TEMRA cells were not expanded in IgG4-RD patients compared to healthy controls. CD4 + SLAMF7 + TEM cells (but not TEMRA cells) were significantly increased among IgG4-RD patients. Within CD4 + SLAMF7 + TEM cells, CD8α - but not CD8α low cells were elevated in IgG4-RD patients. The same dominant clones of CD8α - CD4 + SLAMF7 + TEM cells found in the peripheral blood were also identified in affected tissue. Both CD8α - and CD8α low CD4 + SLAMF7 + TEM cells expressed cytolytic molecules. Clonally expanded CD8α - but not CD8α low CD4 + SLAMF7 + TEM cells decreased following glucocorticoid-induced disease remission. Conclusions: A subset of CD8α - CD4 + SLAMF7 + cytotoxic TEM cells is oligoclonally expanded in patients with active IgG4-RD. This population contracts following glucocorticoid-induced remission. Further characterisation of this cell population may provide prognostic information and targets for therapeutic intervention. References: [1] Della-Torre E, Lanzillotta M, Doglioni C. Immunology of IgG4-related disease. Clin Exp Immunol. 2015;1881:191–206. [2] Mattoo H, Della-Torre E, Mahajan VS, Stone JH, Pillai, S. Circulating Th2 memory cells in IgG4-Related Disease are restricted to a defined subset of subjects with atopy. Allergy2014;69:399–402. [3] Mattoo H, Mahajan VS, Maehara T, Deshpande V, Della-Torre E, Wallace ZS, et al. Clonal expansion of CD4+ cytotoxic T lymphocytes in patients with IgG4-Related DIsease. J Allergy Clin Immuno. 2016;138:825–38. [4] Maehara T, MAttoo H, Ohta M, Mahajan VS, Moriyama M, Yamauchi M, et al. Lesional CD4+ IFN-γ+ cytotoxic T lymphocytes in IgG4-Related DIsease dacryoadenitis and sialoadenitis. Ann Rheum Dis. 2017;76:377–385. Acknowledgements: Fondazione Italiana per la Ricerca sull'Artrite (FIRA Onlus) Disclosure of Interest: None declared